Survey of Campylobacter in foods implicated in foodborne diseases in Southern Brazil - Bessa, Marjo Cadó (2020)
Campylobacter is not routinely tested in foodborne disease investigations in Brazil. Here, we studied the occurrence of Campylobacter among other food-related bacteria commonly found in foodborne disease outbreaks reported in Rio Grande do Sul State, Southern Brazil. Seventy-two food samples were analyzed by using culture-based detection methods during the 18-month investigation of 36 foodborne disease outbreaks. The sampled foods from the foodborne disease outbreaks were all negative for Campylobacter. However, at least one of other routinely investigated foodborne-related bacteria was detected in 29.17% (21/72) of the samples. Taken together, these results suggest the need to monitor Campylobacter in foodborne diseases to detect sporadic cases caused by Campylobacter that might go unnoticed in Rio Grande do Sul.